2008
DOI: 10.1513/pats.200709-148et
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities in Chronic Obstructive Pulmonary Disease

Abstract: Comorbidities such as cardiac disease, diabetes mellitus, hypertension, osteoporosis, and psychological disorders are commonly reported in patients with chronic obstructive pulmonary disease (COPD) but with great variability in reported prevalence. Tobacco smoking is a risk factor for many of these comorbidities as well as for COPD, making it difficult to draw conclusions about the relationship between COPD and these comorbidities. However, recent large epidemiologic studies have confirmed the independent detr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
278
1
18

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 394 publications
(310 citation statements)
references
References 117 publications
13
278
1
18
Order By: Relevance
“…The reported prevalence of diabetes among patients with COPD ranges from 1.6 to 16% in western countries, and there is evidence of an interaction between diabetes and COPD (Chatila et al 2008). However, our study, which included patients with COPD with a first hospitalization, appeared to have higher a HR, hazard ratio; CI, confidence interval.…”
Section: Discussionmentioning
confidence: 99%
“…The reported prevalence of diabetes among patients with COPD ranges from 1.6 to 16% in western countries, and there is evidence of an interaction between diabetes and COPD (Chatila et al 2008). However, our study, which included patients with COPD with a first hospitalization, appeared to have higher a HR, hazard ratio; CI, confidence interval.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies conducted reported that the anemia prevalences in COPD are 23%, 21%, and 15%. 6,11 Anemia could be caused by many conditions or diseases, including bleeding, malignancies, chronic kidney disease (CKD). Those conditions or diseases were found in subjects in this study and there was no control over those conditions.…”
Section: Figure 4 Proportion Of Comorbidity According To Smoking Historymentioning
confidence: 99%
“…It supports the previous study in which the prevalence of DM type 2 in COPD patients is between 1.6-16%. 6 Based on several studies, diabetes in COPD is caused by pro-inflammatory cytokine (TNF-α and IL-6) which can block signal through insulin receptor; as the result, insulin resistance is occurred. Therefore, COPD patient has a higher risk to have DM type 2.…”
Section: Figure 4 Proportion Of Comorbidity According To Smoking Historymentioning
confidence: 99%
See 1 more Smart Citation
“…KOAH'ın prevelansının yüksek olmasına bağlı olarak, KOAH'a bağlı pulmoner hipertansiyon (PH), PH nedenlerinin arasında en sık görü-len nedenlerinden biridir (1). Yapılan çalışmalarda, KOAH tanılı olgularda PH prevelansı %30-70 arasın-da bulunmuştur (2)(3)(4). Bu olguların çoğunun, ortalama pulmoner arter basıncı (PAB) 20-35 mmHg iken, olguların %3-5'inde 35-40 mmHg arasında olduğu görülmüştür (5).…”
Section: Introductionunclassified